Redox Imbalance and Mitochondrial Abnormalities in Kidney Disease - Liang-Jun Yan (Biomolecules, 2022)
The kidneys carry out fundamental life-sustaining functions by removing waste substances, controlling salt and water balance, retaining substances vital to the body such as glucose and proteins, and maintaining blood pH balance [...]